W.C. Fields comedies - Fields, W. C. (William Claude), 1880-1946.
Typescripts of unpublished comedies.
Typescripts.
Humorist, actor, and entertainer; original surname: Dukenfield.
Collection material in English.
Keywords: American wit and humor; American drama (Comedy); Humorists